2011
DOI: 10.3928/1081597x-20101201-02
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Wound Healing After Ultraviolet-A/Riboflavin Collagen Cross-Linking: A Rabbit Study

Abstract: Riboflavin+UVA CXL triggers more anterior keratocyte apoptosis than corneal scrape with UVA alone or riboflavin alone. Inflammation monitored by the monocyte marker CD11b was present, but not statistically different among the three groups. Very little myofibroblast generation could be detected after UVA+riboflavin CXL, indicating that the mild stromal haze associated with this procedure is normally related to transient corneal fibroblast generation rather than more persistent haze due to generation of myofibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 22 publications
2
32
0
2
Order By: Relevance
“…Other surgical insults such as PRK or epithelial debridement can also lead to keratocyte apoptosis but this is usually confined to the more superficial layers (50-75 lm) [19]. Therefore, although some of these changes could be attributed to the epithelial injury but recent ex vivo studies have demonstrated higher rates of keratocyte apoptosis in standard CXL (with epithelial removal) than corneal epithelial removal with either UVA or riboflavin alone [20]. These reports are consistent with our results indicating that CXL has indeed significant impact on corneal stroma and keratocyte apoptosis helping to remodel a firmer microstructure.…”
Section: Discussionmentioning
confidence: 99%
“…Other surgical insults such as PRK or epithelial debridement can also lead to keratocyte apoptosis but this is usually confined to the more superficial layers (50-75 lm) [19]. Therefore, although some of these changes could be attributed to the epithelial injury but recent ex vivo studies have demonstrated higher rates of keratocyte apoptosis in standard CXL (with epithelial removal) than corneal epithelial removal with either UVA or riboflavin alone [20]. These reports are consistent with our results indicating that CXL has indeed significant impact on corneal stroma and keratocyte apoptosis helping to remodel a firmer microstructure.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of CXL are considered to consist of two phases, first the photochemical reaction and then the wound healing response (Salomao et al 2011;Touboul et al 2012). A corneal demarcation line was seen in a majority of the patients in both treatment groups, as a sign of a crosslinking wound healing response (Seiler & Hafezi 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although the section "Translational Science" is new, the Journal has published a number of articles in past years that would have been ideal candidates for such a section. [6][7][8][9][10][11] The inaugural Translational Science article in this month's issue is from Santhiago and colleagues on short-term cell death and infl ammation after intracorneal inlay implantation in rabbits. 12 Although not all scientists are in agreement with the promotion of this term, the Journal aims to provide different outlooks and modern usage of translational research in this way to advance the fi eld of refractive surgery.…”
Section: Discussionmentioning
confidence: 99%